Emission and Noise Characteristics of a Diesel Engine Fuelled with Diesel-Chicken Oil Biodiesel Blends - Khaskheli, A. A.; Arain, H. J.; Memon, I. A.; Rajput, U. A.; Ahsan, M. J. (Engineering, Technology & Applied Science Research, 2020)
Biodiesel is a significant renewable, safe, and environmentally friendly source of energy that produces a lesser amount of greenhouse effect gasses. The studied biodiesel source is local chicken frying oil, synthesized by the trans-esterification process. In this research, the Particulate Matter (PM) exhaust gas emissions and sound emissions are examined. Emissions such as PM (PM1.0, PM2.5, PM7.0, and PM10), nitric oxides (i.e. NO and NO2), CO, CO2, and noise were investigated at variable loads with constant engine speed. Fuel samples, i.e. pure diesel (D100) and 20% Biodiesel (B20) and 30%Biodiesel (B30) blends were tested. Conventional diesel was found to emit more particulate and sound emissions, while B30 had lower emissions than B20 and conventional diesel. The lowest average values regarding exhaust gas emissions were 0.00690ppm for PM1.0, 7.44ppm for NO2 was, and 190.727ppm for CO, presented in B30. However, emissions from the engine decreased with an increase in the blending ratio of biodiesel. Furthermore, the lowest average value of CO2 was found in B30 and was about 1.457%.